State Registration In The Mechanism Of Administrative And Legal Regulation - Kovbas, Ihor (Baltic Journal of Economic Studies, 2022)
The subject of the study is administrative and legal relations in the field of state registration. Methodology. The methodological basis of the study are methods of induction and deduction, dialectical- materialistic method, the method of analysis and synthesis, the historical method, which allowed to objectively understand the content and essence of the issues under study. The purpose of the article is the development of theoretical and methodological provisions, as well as the development of practical recommendations to improve the process of providing state registration services. The results of the study showed that the current state of the public services sector is characterized by uneven development and use of modern forms and methods of their management. Administrative-procedural legal relations in the field of state registration are social relations regulated by administrative-procedural law, which develop in connection with the realization of a subjective right to material or non-material goods (objects) and the participants of which are, on the one hand, a legal or physical person, on the other hand – a state subject of registration. Conclusion. It should be noted that the legislation regulating the procedure for registration of legal entities is largely imperfect and makes the regulation of the relations in question ineffective. This also applies to other normative legal acts regulating other types of state registration. Improvement of legislation will improve the level of legal protection of constitutional rights and obligations of citizens and organizations. Thus, the ways and methods of solving problems that have developed in the sphere of state registration should become an integral part of the whole, based on the priority directions of modern administrative reform. Such directions, in our opinion, are: limitation of state interference in economic activities of business entities, including termination of excessive state regulation; elimination of duplication of functions and powers of state executive authorities; development of self-regulatory organizations in the sphere of economy; organizational separation of functions related to the regulation of economic activity, supervision and control, management of state property and the provision of state organizations of services to citizens and legal entities; completion of the process of separation of powers between state executive bodies of Ukraine, optimization of territorial bodies of executive power.
Keywords: administrative law; administrative legislation; state registration; legal institution, public admini- stration; legal entities, entrepreneurs; legal mechanism; administrative procedures; registration authority